Water users' associations in Central Asia: opportunities and challenges for development [Abstract only] - Mukhamedova, Nozilakhon; Anarbekov, Oyture (2015)
The presentation first guides to the challenges of water management. First are old challenges related poor conditions and physical deterioration of irrigation and drainage systems; while new ones such as the rising number of farming units not aligned with hydraulic boundaries; variety of crops grown therefore diverging irrigation schedules; mismatch between on-farm irrigation system and smaller farming units; and dissolution of former water management units of collective farms. In the next part of the presentation we provide a cross-country comparison of water reforms implemented by international donor community in the region. As we will show most of WUAs are not water users driven, they have been established via big bang campaigns of governments and donors within the borders of former collective farms without taking into account local context of irrigation and farming. We conclude that the major constraints for the consistency and improved performance of water user groups are found in uneven implementation of water reforms and in some countries, reluctance to change within each country, weak legal basis for the responsibilities and water rights of WUAs, sustainability issues connected with water services pricing and inclusion and obligations of water users.